2014
DOI: 10.1186/1749-7922-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Successful interventional management of abdominal compartment syndrome caused by blunt liver injury with hemorrhagic diathesis

Abstract: We report that a case of primary abdominal compartment syndrome (ACS), caused by blunt liver injury under the oral anticoagulation therapy, was successfully treated. Transcatheter arterial embolization (TAE) was initially selected, and the bleeding point of hepatic artery was embolized with N-Butyl Cyanoacylate (NBCA). Secondary, percutaneous catheter drainage (PCD) was performed for massive hemoperitoneum. There are some reports of ACS treated with TAE. However, combination treatment of TAE with NBCA and PCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Decompression and hemorrhage control are essential treatments for HCS. In previous reports, needle drainage or surgical decompression was performed for decompression [ 4 , [6] , [7] , [8] ], and surgical hemostasis or angioembolization was conducted for hemorrhage control [ 6 , 7 , 9 ]. However, the number of such reported cases is limited, and sufficient evidence has not been established for the management of this complicated condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decompression and hemorrhage control are essential treatments for HCS. In previous reports, needle drainage or surgical decompression was performed for decompression [ 4 , [6] , [7] , [8] ], and surgical hemostasis or angioembolization was conducted for hemorrhage control [ 6 , 7 , 9 ]. However, the number of such reported cases is limited, and sufficient evidence has not been established for the management of this complicated condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, several disadvantages associated with nonoperative management have been reported: risk of missed intra-abdominal injury; transfusion-related illness; and risks associated with embolization techniques including hepatic necrosis, abscess formation, and bile leak [ 3 ]. Reports have found that intrahepatic or subcapsular hematoma can increase intrahepatic pressure, excluding the portal vein and inferior vena cava, resulting in marked hepatic dysfunction and obstructive shock in patients with hepatic injury who were treated nonoperatively [ [4] , [5] , [6] , [7] , [8] ]. This pathological condition has been described as hepatic compartment syndrome ( HCS ) and is most commonly reported in young patients with hard hepatic capsules [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several disadvantages associated with nonoperative management have been reported: risk of missed intraabdominal injury; transfusion-related illness; and risks associated with embolization techniques including hepatic necrosis, abscess formation, and bile leak (3). Reports have found that intrahepatic or subcapsular hematoma can increase intrahepatic pressure, excluding the portal vein and inferior vena cava, resulting in marked hepatic dysfunction and obstructive shock in patients with hepatic injury who were treated nonoperatively (4)(5)(6)(7)(8). This pathological condition has been described as hepatic compartment syndrome (HCS) and is most commonly reported in young patients with hard hepatic capsules (9).…”
Section: Introductionmentioning
confidence: 99%